2021
DOI: 10.1002/advs.202004762
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Rare‐Earth Tritelluride Quantum Materials: Structure, Properties, and Synthesis

Abstract: A distinct class of 2D layered quantum materials with the chemical formula of RTe3 (R = lanthanide) has gained significant attention owing to the occurrence of collective quantum states, superconductivity, charge density waves (CDW), spin density waves, and other advanced quantum properties. To study the Fermi surface nesting driven CDW formation, the layered RTe3 family stages an excellent low dimensional genre system. In addition to the primary energy gap feature observed at higher energy, optical spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 98 publications
(206 reference statements)
0
20
0
Order By: Relevance
“…This causes larger in-plane lattice constant anisotropy and higher T CDW moving from Tb to La. 12 Fig. 4a summarizes the pressure required to cross over from CDW to non-CDW phase across the entire RTe 3 series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes larger in-plane lattice constant anisotropy and higher T CDW moving from Tb to La. 12 Fig. 4a summarizes the pressure required to cross over from CDW to non-CDW phase across the entire RTe 3 series.…”
Section: Resultsmentioning
confidence: 99%
“…2 More recent studies have shown the presence of the light-induced CDW phase, 8 and thickness-dependent CDW properties, 9 and established GTe 3 as a high carrier mobility material with unique magnetic ordering. 10,11 Lately, much effort has been given to understanding the CDW phase behavior, which is hosted within the Te atomic layers 12 and driven not only by Fermi surface nesting 3 but also by strong electron–phonon interaction. 13,14 Here the two Te layers are separated by the RTe slab, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[13,19,20] Overall, RTe 3 materials exhibit CDW phase transition temperature (T CDW ) ranging from below room temperature (220 K for TmTe 3 ) to well-above room temperature (550 K for LaTe 3 ) across the entire lanthanide series. [11,14] For practical applications of RTe 3 materials, however, their air stability plays a critical role that ultimately dictates the reliability and lifetime of the device. Because of their large surfaceto-volume ratio, 2D materials and even vdW layered crystals raise concerns regarding their stability.…”
Section: Introductionmentioning
confidence: 99%
“…One of the examples of this class of vdW CDW crystals is the lanthanide tritellurides series with the chemical formula of rare-earth tritellurides (RTe 3 ), where R stands for the rare-earth elements from La to Tm. [11] Previous studies have shown the emergence of temperature-driven CDW phase in RTe 3 based on Raman spectroscopy, [12,13] electrical resistivity measurements, [4,14] angle-resolved photoelectron spectroscopy (ARPES), [15,16] as well as electron diffraction. [17,18] The presence of the CDW state was attributed to the Fermi surface nesting or strong electron-phonon interaction and can be accompanied by the Kohn anomaly.…”
Section: Introductionmentioning
confidence: 99%
“…Various aspects of charge density wave transitions in RE tritellurides are discussed in [7]. Within this family, TbTe 3 stands out as material evidencing three successive magnetic phase transitions at T N1 = 6.6 K, T N2 = 5.6 K, and T N3 = 5.4 K ascribed to the interplay of magnetism with charge density waves [8].…”
Section: Introductionmentioning
confidence: 99%